Assessment of the Impact of GDP, Employment, and Unemployment on the Human Development Index (HDI) for Western Balkan Countries (2006-2023) - Nazarko, Blerta Kristo; Hoxha, Sofije (European Scientific Journal, ESJ, 2025)
This study analyzes and presents the concrete relationships that emerge from the reciprocal linkages between the Human Development Index (HDI) and GDP per capita (constant 2015 US), Unemployment, total (% of total labor force) (modeled ILO estimate), and the Employment-to-population ratio, 15+, total (%) (modeled ILO estimate), for Western Balkan countries during the period 2006-2023. The study also examines the correlation between the ranking positions of GDP and HDI for each Western Balkan country. Based on regression analyses, the results indicate that the upward trend of GDP per capita (constant 2015 US) is significant for the upward tendencies of HDI, but is not a sufficient condition on its own to explain HDI growth patterns. Moreover, deviations-although not substantial-from annual ranking positions display a highly significant correlation. The weight of GDP’s impact on HDI, despite varying among the Western Balkan countries, ranges between 71.38% (Albania) and 88.02% (Bosnia and Herzegovina), while the rank correlation coefficients between these two variables range from 0.875 to 0.980. Additionally, it can be stated that the (positive) impact weight of the Employment-to-population ratio, 15+, total (%) (modeled ILO estimate), on HDI also differs noticeably across Western Balkan countries, ranging from 27.67% to 72.11%. Meanwhile, the negative impact of unemployment on HDI likewise shows evident variation among countries. Separate analyses were conducted for each Western Balkan country included in the study, as well as a comprehensive comparative analysis.